THE MODEL OF ISLAMIC EDUCATION DURING THE PROPHET MUHAMMAD’S ERA AND ITS RELEVANCE IN THE MODERN ERA - Mahrus Mahrus; Yuliana Habibi; Abdullah Ibrahim (Istifkar: Media Transformasi Pendidikan, 2025)
Islamic education during the Prophet Muhammad’s era served as the primary foundation for building a faithful and God-conscious society. This study aims to describe the model of Islamic education implemented in Makkah and Madinah and its relevance in the modern era. The research employed a qualitative descriptive method with content analysis applied to various relevant documents. The findings reveal a clear distinction between the two phases of education. In Makkah, education emphasized the strengthening of faith and monotheism (tawhid), aiming to instill the values of divine unity within each Muslim so that they were reflected in daily behavior. Meanwhile, education in Madinah focused more on social and political aspects as a continuation of tawhid-based education, positioning Islamic teachings as the foundation of community life. The model of education in the Prophet’s era holds significant relevance for contemporary Islamic education, particularly in integrating spiritual, moral, and social values to address the challenges of modernity.